Physiological mechanisms of lysophosphatidylcholine-induced de-ramification of murine microglia - Schilling, Tom (Blackwell Science Inc, 2004)
Activation of microglial cells, the resident macrophages of the brain, occurs rapidly following brain injury. De-ramification, i.e. transformation from ramified into amoeboid morphology is one of the earliest manifestations of microglial activation. In the present study, we identified the physiological mechanisms underlying microglial de-ramification induced by lysophosphatidylcholine (LPC). Patch-clamp experiments revealed activation of non-selective cation currents and Ca(2+)-dependent K(+) currents by extracellular LPC. LPC-activated non-selective cation channels were permeable for monovalent and divalent cations. They were inhibited by Gd(3+), La(3+), Zn(2+) and Grammostola spatulata venom, but were unaffected by diltiazem, LOE908MS, amiloride and DIDS. Ca(2+) influx through non-selective cation channels caused sustained increases in intracellular Ca(2+) concentration. These Ca(2+) increases were sufficient to elicit charybdotoxin-sensitive Ca(2+)-dependent K(+) currents. However, increased [Ca(2+)](i) was not required for LPC-induced morphological changes. In LPC-stimulated microglial cells, non-selective cation currents caused transient membrane depolarization, which was followed by sustained membrane hyperpolarization induced by Ca(2+)-dependent K(+) currents. Furthermore, LPC elicited K(+) efflux by stimulating electroneutral K(+)–Cl(−) cotransporters, which were inhibited by furosemide and DIOA. LPC-induced microglial de-ramification was prevented by simultaneous inhibition of non-selective cation channels and K(+)–Cl(−) cotransporters, suggesting their functional importance for microglial activation.